2021
DOI: 10.3390/polym13203503
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Valorization of Fruit and Vegetable Wastes: Active Packaging, Biocomposites, By-Products, and Innovative Technologies Used for Bioactive Compound Extraction

Abstract: According to the Food Wastage Footprint and Climate Change Report, about 15% of all fruits and 25% of all vegetables are wasted at the base of the food production chain. The significant losses and wastes in the fresh and processing industries is becoming a serious environmental issue, mainly due to the microbial degradation impacts. There has been a recent surge in research and innovation related to food, packaging, and pharmaceutical applications to address these problems. The underutilized wastes (seed, skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 249 publications
(247 reference statements)
0
24
0
1
Order By: Relevance
“…The fruit‐processing industry also generates huge amounts of waste and byproducts that are potential sources of different bioactive compounds (dietary fibers, amylopectin, protein, phenolics, carotenoids), vitamins, oils, and minerals (micronutrients), which serve as antimicrobial, antioxidant, anticancer, and anti‐cardiovascular disease substances for humans 11,12,26,27,62 . Basri et al ., 63 Lee et al ., 16 Miller et al ., 64 and Mohsen et al 62 . also confirmed that these byproducts contain free fatty acids (saturated and unsaturated) and minerals like sodium (Na), magnesium (Mg), phosphorus (P), potassium(K), and calcium (Ca), which serve as ingredients in food supplements, animal feed, and for the production of different biofuels such as biodiesel and ethanol.…”
Section: Tropical Fruit‐processing Waste/byproducts and Compositionmentioning
confidence: 99%
“…The fruit‐processing industry also generates huge amounts of waste and byproducts that are potential sources of different bioactive compounds (dietary fibers, amylopectin, protein, phenolics, carotenoids), vitamins, oils, and minerals (micronutrients), which serve as antimicrobial, antioxidant, anticancer, and anti‐cardiovascular disease substances for humans 11,12,26,27,62 . Basri et al ., 63 Lee et al ., 16 Miller et al ., 64 and Mohsen et al 62 . also confirmed that these byproducts contain free fatty acids (saturated and unsaturated) and minerals like sodium (Na), magnesium (Mg), phosphorus (P), potassium(K), and calcium (Ca), which serve as ingredients in food supplements, animal feed, and for the production of different biofuels such as biodiesel and ethanol.…”
Section: Tropical Fruit‐processing Waste/byproducts and Compositionmentioning
confidence: 99%
“…The main purpose is to increase food quality and shelf-life. The most common additives are moisture absorbers, gas scavengers, carbon dioxide emitters, antioxidant, and antimicrobial compounds [ 152 ]. Related to food packaging obtained from F&V by-products, companies present a special interest due to the interest of circular economy and zero waste strategies around the world during last years.…”
Section: Trends and Challenges For Fruit And Vegetable By-products Application In Food Systemsmentioning
confidence: 99%
“…On the other hand, the colorimetric pH indicator films can be a potential tool for obtaining smart packaging, showing alterations of the food pH by food deterioration and environmental changes. Then, consumers receive authentic information regarding the food’s quality and its edibility (fresh, spoiling, and spoiled product such as milk) [ 152 ]. For example, an interesting way to use anthocyanins is building an active use by-date indicator for milk.…”
Section: Trends and Challenges For Fruit And Vegetable By-products Application In Food Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, bioactive compounds present in the waste of the citrus industry emerge as potential prebiotic ingredients [ 9 ]. These compounds could also have applications in food stabilisation because they help inhibit oxidation (lipid and protein) and the growth of pathogenic and deteriorating bacteria in the food supply [ 10 ]. Therefore, investigating the possibility of reintroducing it into the human food chain would help add value to it and improve this industry’s efficiency.…”
Section: Introductionmentioning
confidence: 99%